(untitled) (Vallis Aurea, 2020)
The main objective of this paper is to determine total investments by activities in Brod-Posavina County, revenues and expenditures level, number of entrepreneurs by activities, including the achieved financial results of entrepreneurs of the Brod-Posavina County over the past five years. During research of facts and possibilities that currently exist, the following research methods are used in a different combination: historical method, the method of analysis and synthesis, classification, description method and generalization.